The Impact of Prebiotics, Probiotics and Synbiotics on Metabolic Syndrome and Chronic Diseases: A Review - Gayatri Ganu; Dheeraj Nagore; Shital Rede; Rishika Lohani; Nayan Chaudhari (International Journal of Nutrition Sciences, 2025)
Metabolic syndrome is characterized by a cluster of metabolic abnormalities, including insulin resistance, hypertension, dyslipidemia, and abdominal obesity, which significantly increase the risk of cardiovascular disease and type 2 diabetes. Emerging evidence suggests that metabolic syndrome may play a critical role in the cancer progressionand contribute to higher mortality rates. Emerging researches highlight the essential role of the gut microbiota in maintaining health, with dysbiosis being linked to various chronic diseases. This review focused on the potential therapeutic roles of prebiotics, probiotics, and synbiotics in the management and prevention of metabolic syndrome and its associated conditions. Prebiotics support the growth of beneficial gut bacteria, while probiotics are live microorganisms that confer health benefits. Synbiotics, combinations of prebiotics and probiotics, have demonstrated promise in improving gut health and managing metabolic disorders. The article synthesizes clinical and preclinical evidences regarding the effects of these supplements on obesity, diabetes, cancer, inflammatory bowel disease, cardiovascular diseases, and diarrhea. It reviews the efficacy of specific prebiotics (such as inulin and fructooligosaccharides), probiotics (like Lactobacillus and Bifidobacterium), and synbiotics, highlighting their mechanisms of action and clinical outcomes. Additionally, the review emphasized the need for more rigorous clinical trials to establish the safety, efficacy, and optimal use of these supplements in the management of metabolic and chronic diseases.In conclusion, prebiotics, probiotics, and synbiotics hold significant potential for improving metabolic health and managing chronic diseases. Future researches should prioritize well-designed clinical trials to fully explore their therapeutic potential and refine treatment strategies.